Experimental insights into Stannern‐trend eucrite petrogenesis. (22nd May 2018) - Crossley, S. D.; Lunning, N. G.; Mayne, R. G.; McCoy, T. J.; Yang, S.; Humayun, M.; Ash, R. D.; Sunshine, J. M.; Greenwood, R. C.; Franchi, I. A.
Abstract: The incompatible trace element‐enriched Stannern‐trend eucrites have long been recognized as requiring a distinct petrogenesis from the Main Group‐Nuevo Laredo (MGNL) eucrites. Barrat et al. (2007 ) proposed that Stannern‐trend eucrites formed via assimilation of crustal partial melts by a MGNL‐trend magma. Previous experimental studies of low‐degree partial melting of eucrites did not produce sufficiently large melt pools for both major and trace element analyses. Low‐degree partial melts produced near the solidus are potentially the best analog to the assimilated crustal melts. We partially melted the unbrecciated, unequilibrated MGNL‐trend eucrite NWA 8562 in a 1 atm gas‐mixing furnace, at IW‐0.5, and at temperatures between 1050 and 1200 °C. We found that low‐degree partial melts formed at 1050 °C are incompatible trace element enriched, although the experimental melts did not reach equilibrium at all temperatures. Using our experimental melt compositions and binary mixing modeling, the FeO/MgO trend of the resultant magmas coincides with the range of known Stannern‐trend eucrites when a primary magma is contaminated by crustal partial melts. When experimental major element compositions for eucritic crustal partial melts are combined with trace element concentrations determined by previous modeling (Barrat et al.2007 ), the Stannern‐trend can be replicated with respect to both major, minor, and trace element concentrations.